2007
DOI: 10.1094/cchem-84-4-0415
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Starch from Alkaline Cooked Corn Masa

Abstract: Starch granules undergo structural and morphological changes during food processing unit operations as they interact with other food ingredients. This study was conducted to isolate and characterize starch granules from corn masa. A proteolytic enzyme, thermolysin, was effective in separating and isolating starch granules from endosperm proteins present in masa. The efficiency of starch extraction using thermolysin was 74% (w/w), and subsequent analyses showed that the isolated granules were free of contaminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
5
12
0
Order By: Relevance
“…These samples presented higher totopo elastic moduli (hardness) compared with the other maize samples. The data shown in Table III are in agreement with previous published reports that indicated that traditional nixtamalized products presented higher thermal properties than raw samples (Campus-Baypoli et al 1999;Rendón-Villalobos et al 2002;Ratnayake et al 2007). In the hybrid and Tuxpeño samples, most of starch granules presented a high degree of gelatinization (90%) that increased the hardness in totopos.…”
Section: Resultssupporting
confidence: 91%
“…These samples presented higher totopo elastic moduli (hardness) compared with the other maize samples. The data shown in Table III are in agreement with previous published reports that indicated that traditional nixtamalized products presented higher thermal properties than raw samples (Campus-Baypoli et al 1999;Rendón-Villalobos et al 2002;Ratnayake et al 2007). In the hybrid and Tuxpeño samples, most of starch granules presented a high degree of gelatinization (90%) that increased the hardness in totopos.…”
Section: Resultssupporting
confidence: 91%
“…The peak present at 930.0 to 931.1 cm −1 attributed to skeletal mode vibration of α‐1,4 glycosidic linkage (C─O─C). The peaks present at 861.5 and 765 cm −1 attributed to ─CH 2 deformation and C─C stretching (Ghoshal & Mehta, ; Singh & Kaur, ; Ratnayake, Wassinger, & Jackson, ; Ratnayake et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a full 76% of the starch granules were not physically altered (Ratnayake et al 2007). Previously, during traditional masa preparation, a low percentage of the granules gelatinized either fully or in part during normal cooking.…”
Section: Sensory Evaluationmentioning
confidence: 88%